Contribution of livestock production to food and nutritional security and to the reduction of poverty in Latin America and the Caribbean - D?az, T. (Cuban Journal of Agricultural Science, 2014)
It is an honor sharing in this opening session of the most important meeting on Animal Sciences in Latin America with you, thanks to the kind invitation of the Organizing Committee of ALPA to whom I thank and as always, it is a pleasure to go back to Cuba and enjoy myself with the culture, human warmth and kindness of the Cuban people